THE ROLE OF LOGIC IN CRITICAL THINKING - Nataliia Reva (Cхід, 2020)
The article focuses on two things: the main difference between Critical thinking and Logic as the academic subjects and between Critical thinking and Logical thinking as two somehow similar, but nevertheless, diverse ways of rational thinking. The author stands that the false association of these two thinking manners influence on how both disciplines are taught. Unfortunately, in Ukraine, Critical thinking is neglected. Often Ukrainian universities replace it with some courses on Formal and Informal Logic. Furthermore, the existing Ukrainian manuals on Critical thinking are all devoted only to the logical issues. Although Logic can give some significant and useful tools, the author emphasizes that it is not sufficient for the correct usage of Critical thinking. Therefore, the author analyzes the main characteristics of Critical and Logical thinking. Using the table method, the authors indicate which features both thinking manners have in common and which are different for them. This table of comparison clearly demonstrates that Critical thinking and Logical thinking are not the same. Moreover, the author shows the roots of the established terminological misunderstanding in human society by studying the history of two subjects: Critical thinking and Informal Logic. Western science had already divided these disciplines and identified the main priorities and challenges for each. However, in Ukraine, we still have some “separation problems”, because of the glossary absence and the false association of two ways of rational thinking. To prove the declared similarity wrong the author studies two recently widespread fake news about COVID-19. The author debunks both COVID-myths by using different means given by Logic and Critical thinking showing that both of them can be used independently one of each other. The author stands that Critical Thinking is a very important skill, especially, during a pandemic time. Therefore, it is extremely important that it is taught and used in the correct manner.